Six-Sigma approach to improve industry engagement strategies in Malaysian apprenticeship program - Abdullah, Roziyati; Leman, Zulkiflle; Baharudin, B.T Hang Tuah; Ahmad, Siti Azfanizam (International Journal of Evaluation and Research in Education (IJERE), 2025)
This empirical study develops an industry engagement model (IEM) by using the Six-Sigma define, measure, analyze, improve, and control (DMAIC) methodology to investigate the key strategies to enhance industry participation (IP) in the Malaysian apprenticeship program known as the National Dual Training System (NDTS). The relationship between five strategies, namely financial incentives (FI), digital administration (DA), productive collaboration (PC), flexible implementation (FT), and efficient promotion (EP) on IP, was examined. The 204 returned questionnaires were analyzed using partial least square-structural equation modelling (PLS-SEM). The findings reveal that FT, EP, and DA strongly influence IP in the NDTS program. In contrast, improvement in FI and PC has little impact on industry involvement. The development of IEM by demonstrating the DMAIC concept is novel and new to the research. It offers enormous potential and value in improving policymakers’ decision-making in apprenticeship programs. It may also be extended to other areas of education in the future.